British-English norms and naming times for a set of 539 pictures: the role of age of acquisition. - Johnston, R; Dent, K; Humphreys, G; Barry, C (2010)
In the present study, we presented picture-naming latencies along with ratings for a set of important characteristics of pictures and picture names: age of acquisition, frequency, picture-name agreement, name agreement, visual complexity, familiarity, and word length. The validity of these data was established by calculating correlations with previous studies. Regression analyses show that our ratings account for a larger amount of variance in RTs than do previous data. RTs were predicted by all variables except complexity and length. A complete database presenting details about all of these variables is available in the supplemental materials, downloadable from http://brm.psychonomic-journals.org/content/supplemental.